Smart City Regulatory Design: Balancing Public Safety, Privacy, and Civil Liberties in Administrative Law - Paramita Andiani; Auliya Citra; Irwan Amar (Westscience Press, 2026)
This study examines the regulatory design of smart city governance in Indonesia through a normative legal approach, with a focus on balancing public safety, privacy, and civil liberties within the framework of administrative law. The rapid adoption of digital technologies—such as surveillance systems, big data analytics, and automated decision-making—has enhanced governmental capacity in delivering public services and maintaining security. However, these developments also raise significant legal challenges related to data protection, administrative discretion, and the potential infringement of fundamental rights. This research analyzes relevant legal frameworks, including constitutional provisions, administrative law principles, and sectoral regulations on digital governance and personal data protection. The findings reveal that Indonesia’s current regulatory framework is fragmented and lacks comprehensive integration, resulting in an imbalance that tends to prioritize public safety and administrative efficiency over privacy and civil liberties. The study identifies key challenges, including weak implementation of data protection principles, limited transparency in algorithmic governance, and inadequate oversight mechanisms. From an administrative law perspective, principles such as legality, proportionality, transparency, accountability, and legal certainty have not been fully operationalized in smart city policies. This study proposes a more integrated and principles-based regulatory model that harmonizes existing regulations, strengthens institutional coordination, and embeds human rights safeguards into digital governance. By aligning smart city development with the rule of law and constitutional values, the study contributes to the formulation of a balanced regulatory framework that supports technological innovation while protecting individual rights in Indonesia.